Dapatkah Tamar Berbicara? (Kajian Hermeneutik Poskolonial Feminis Terhadap Teks 2 Samuel 13:1-22 dalam Perspektif Pengalaman “Kawin Tangkap” di Sumba) - Lena, Iston Umbu Kura; Setyawan, Yusak Budi; Tampake, Tony Robert Christian (IAKN Ambon, 2024)
Women in a patriarchal culture are always required to be submissive, obedient, and silent. Therefore, when women become victims of forced marriage (kawin tangkap) that lead to sexual violence, their voices are silenced as a form of submission and obedience, as experienced by Tamar in the book of 2 Samuel 13:1-22. The purpose of this study is to describe Tamar’s experience as a victim of “forced marriage” by her own brother, Amnon. The research method used is qualitative with a feminist postcolonial hermeneutic study. This approach brings back the experiences of women who have been ignored or silenced to be heard or voiced again. Using Gayatri Chakravorty Spivak’s theory of subaltern, my main argument is that Tamar’s experience as a victim of forced marriage was silenced because of the interests and purpose of men, namely Amnon and Absalom. The result shows that Tamar was able to speak out about her experience, but her voice was silenced, not only because of the patriarchal culture that was so strong in the community but also because of the political interests in it, namely the power struggle between Amnon and Absalom. The conclusion of this research is that the silencing of women’s voices and experiences, namely Tamar as a victim, is the result of a patriarchal culture.